1983
DOI: 10.1029/wr019i001p00001
|View full text |Cite
|
Sign up to set email alerts
|

Daily operation of a multipurpose reservoir system

Abstract: An optimization model that may be used by reservoir system operators to improve daily, real‐time operations and to evolve better long‐term operating guidelines is developed and tested. The four multipurpose reservoirs in the Green River Basin (GRB) of Kentucky are used as a case study. The GRB Operation Optimization Model (GRBOOM) is a linear program constructed to imitate the decision‐ making process that results in actual reservoir release decisions. The model is easily modifiable and very flexible, which al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…Models for long range planning of river basin development using implicit and explicit stochastic streamflow models have been proposed for more than 20 years (e.g., see Houck and Cohon, 1978). Strategies ranging from expert systems to optimization and simulation modeling for incorporating forecast information into real-time operations of complex, multipurpose water resource systems have also been widely developed (e.g., Palmer, et al, 1982;Yazicigil, et al, 1983;Houck, 1992;Sheer, et al, 1992). However, probabilistic tools in general have achieved only limited penetration into the daily world of water resource decision-makers.…”
Section: Acknowledgementmentioning
confidence: 99%
“…Models for long range planning of river basin development using implicit and explicit stochastic streamflow models have been proposed for more than 20 years (e.g., see Houck and Cohon, 1978). Strategies ranging from expert systems to optimization and simulation modeling for incorporating forecast information into real-time operations of complex, multipurpose water resource systems have also been widely developed (e.g., Palmer, et al, 1982;Yazicigil, et al, 1983;Houck, 1992;Sheer, et al, 1992). However, probabilistic tools in general have achieved only limited penetration into the daily world of water resource decision-makers.…”
Section: Acknowledgementmentioning
confidence: 99%
“…The HEC-5 model is considered to be the best documented tool for reservoir simulation of flood and conservation systems [Yeh, 1985]. A significant quantity of work has been published regarding flood operation on reservoirs [Hydrologic Engineering Center, 1976;Sigvaldason, 1976;Yazicigil et al, 1983;Unver and Mays, 1990;Marien et al, 1994;Chang and Chen, 1998;Karbowski et al, 2005;Chang and Chang, 2006;Hsu and Wei, 2007]. However, little literature is available on an early warning model for floods during typhoon attacks, especially considering decision making under uncertainty.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In this paper brief and relevant literature review is presented in the form of various themes. Yazicigil et al (1983) demonstrated a real time operation model on daily basis for Green river basin with four reservoirs. The primary purpose of the reservoir system was flood control with recreation and low flow augmentation as secondary purposes.…”
Section: Literature Reviewmentioning
confidence: 99%